1991
DOI: 10.1002/cber.19911240120
|View full text |Cite
|
Sign up to set email alerts
|

Lithiated 5,6‐Dihydro‐4H‐1,2‐oxazines: Synthesis, Highly Diastereoselective Reactions with Electrophiles, and Subsequent Transformations

Abstract: The 6-(trimethylsilyl)methyl-substituted 1,Zoxazine 1 can smoothly be deprotonated with n-butyllithium at C-4 to give a lithiated species which reacts with a variety of electrophiles to provide the new 1,2-oxazines 5 -16 in good yields. Besides the preparative aspect of these transformations, the high stereoselectivity of many reactions is also interesting from a mechanistic point of view. By deprotonation of the 4-deuterated compound 5a it has been proven that n-butyllithium removes exclusively the proton (or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Deprotonation of oxime ethers by using a strong base such as butyl lithium, and subsequent reaction with a range of electrophiles elaborated the desired product in good yields. [47][48][49][50][51][52][53][54][55] One of the beautiful examples of a-alkylation of oxime ethers has been reported by Caille et al They showed that treatment of (+)-nopinone oxime methyl ether 31 with a wide range of electrophiles in the presence of s-BuLi in THF at À80 C for 10 min gave the corresponding stereoselectively a-alkylated oxime ether 32 in good to high yields. As shown in Scheme 17, due to the stabilization of the carbanion intermediate with the oxygen lone pair of the oxime function, only the E-isomer of 31 able to react through a syn-alkylation process.…”
Section: Regio-and Stereoselective Carbon-carbon (Heteroatom) Bond Fo...mentioning
confidence: 99%
“…Deprotonation of oxime ethers by using a strong base such as butyl lithium, and subsequent reaction with a range of electrophiles elaborated the desired product in good yields. [47][48][49][50][51][52][53][54][55] One of the beautiful examples of a-alkylation of oxime ethers has been reported by Caille et al They showed that treatment of (+)-nopinone oxime methyl ether 31 with a wide range of electrophiles in the presence of s-BuLi in THF at À80 C for 10 min gave the corresponding stereoselectively a-alkylated oxime ether 32 in good to high yields. As shown in Scheme 17, due to the stabilization of the carbanion intermediate with the oxygen lone pair of the oxime function, only the E-isomer of 31 able to react through a syn-alkylation process.…”
Section: Regio-and Stereoselective Carbon-carbon (Heteroatom) Bond Fo...mentioning
confidence: 99%
“…Preparation of 4-Benzoyl-1-diazo-2-oxo-7-octene (20). A solution of 75.8 mL (37.9 mmol) of 0.5 M potassium hexamethyldisilazide in toluene and 45 mL of THF was cooled to −78 °C, and 6.0 g (34.4 mmol) of 1-phenyl-5-hexen-1-one was added. The solution was stirred at −78 °C for 1 h followed by the dropwise addition of 3.91 g (41.3 mmol) of methyl bromoacetate.…”
Section: Methodsmentioning
confidence: 99%
“…As has been already noted, the reaction 3 + 4 → 1 opens the excess predominantly to dihydrooxazines 1 unsubstituted at position C-4 (R 1 = H in Scheme ). However, lithiation of dihydrooxazines 1g (R 1 = H) and subsequent treatment of the resulting anionic species with electrophilic reagent led to various 4-substituted dihydrooxazines 29 in good yields and high stereoselectivity (Scheme , eq 1). …”
Section: Synthesis Of Six-membered Cyclic Oxime Ethers 1 Andmentioning
confidence: 99%